Evaluation of Seven Second Chance Act Adult Demonstration Grantees, December 2001-September 2014 - D'Amico, Ronald ([Verlag nicht ermittelbar], 2018)
These data are part of NACJD's Fast Track Release and are distributed as they were received from the data depositor. The files have been zipped by NACJD for release, but not checked or processed except for the removal of direct identifiers. Users should refer to the accompanying readme file for a brief description of the files available with this collection and consult the investigator(s) if further information is needed. This study evaluates the impacts of re-entry programs developed by seven grantees awarded funds under the Second Chance Act (SCA) Adult Demonstration Program to reduce recidivism by addressing the challenges faced by adults returning to their communities after incarceration. The collection contains 3 SAS data files: admin30.sas(n=966; 111 variables), MIS.sas(n=606; 48 variables), and survey.sas(n=789; 273 variables) and 1 SAS syntax file.